2022
DOI: 10.9734/ejnfs/2022/v14i121283
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional and Functional Properties of Wheat-Defatted Peanut-Orange Peel Composite Flour

Abstract: The need to improve and enhance the nutritional quality of locally made foods (bakery and confectionaries) cannot be overemphasized. This study set out to meet this need by producing composite flours from wheat, defatted peanut and orange peel flour blends which will serve an even greater issue of reducing the cost of wheat importation and use. The samples were coded as follows: A-100:0:0, B-90:5:5, C-85:10:5, D-80:15:5, E-75:20:5 of wheat flour: Defatted peanut flour: orange peel flour. The flours produced we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
0
0
Order By: Relevance
“…The oxalate contents ranged from 0.08 to 0.27 %. There was significant increase in the contents as level of incorporation mango kernel flour increased [37].…”
Section: Anti-nutrient Content Of the Flours And Their Blendsmentioning
confidence: 89%
See 1 more Smart Citation
“…The oxalate contents ranged from 0.08 to 0.27 %. There was significant increase in the contents as level of incorporation mango kernel flour increased [37].…”
Section: Anti-nutrient Content Of the Flours And Their Blendsmentioning
confidence: 89%
“…Interestingly too, the energy content of the flour blend samples ranged from 347.87 kcal in sample F to 376.39 kcal in the control sample (A). There was significant difference (p<0.05) in the energy content of the flour samples as the proportion of MKF and OPF increased [34,35].…”
Section: Proximate Composition Of the Flours And Their Blendsmentioning
confidence: 99%
“…As observed, the complementary food samples bulk density increased with an increase in the incorporation of SBF. Flours from legumes have been reported to have high BD [24] and this could also be one of the reasons for the significant increase (p<0.05) in the BD from sample ComF1 to ComF5. A similar trend was observed by Ojinnaka et al [23].…”
Section: Functional Propeties Of the Complementary Foodmentioning
confidence: 99%
“…Increased heat treatment of a protein leads to a greater hydrophobic nature, attributed to the high exposure of hydrophobic groups due to the unfolding of protein molecules [26]. This further explain the notable rise (p<0.05) in the Oil Absorption Capacity (OAC) of the flours as the substitution of ComF6 increases (ComF6 is generated through a sequence of heat treatment procedures, including roasting) [24]. Hasmadi, M., Noorfarahzilah, M., Noraidah et al [26] reported results on the functional properties of composite flour similar to that of this study agree with those of.…”
Section: Functional Propeties Of the Complementary Foodmentioning
confidence: 99%
“…The proximate parameters were determined using the standard method of Association Official Analytical Chemists [12].…”
Section: Determination Of Proximate Composition Biscuit From Wheat So...mentioning
confidence: 99%